Factors influence employees turnover intentions at Hitachi Chemical (Johor) Sdn. Bhd. / Nur Faridah Mohamad - Mohamad, Nur Faridah (Faculty of Business and Management, 2019)
This study determines whether factors such as job satisfaction and organizational commitment influence employees turnover intention at Hitachi Chemical (Johor) Sdn. Bhd. The questionnaire was the method for data collection with a total of 140 respondents taking part in this study, using a convenient sampling procedure and Statistical Package for Social Science (SPSS) were utilized to analyze the data. Descriptive statistic, correlation, and regression analysis were used in this study for the purposes to find out the relations between the variables. Based on the result, both independent variables which is job satisfaction and organizational commitment have a significant and negative relationship on the dependent variable which is turnover intention. Among all two factors, job satisfaction is found to be the strongest in factor influence turnover intention of employees at Hitachi Chemical (Johor) Sdn. Bhd. The essential consequences of the research work is that, the supervisors or managers must take some creative steps to improve employee’s job satisfaction, to expand organizational commitment, and reduces employee turnover intentions in their organization.